Pluripotency factors and miRNAs in human ovarian cancer cells and their secreted exosomes regulate gene expression and phenotype - Enriquez, Vanessa Ann, author; Bouma, Gerrit J., advisor; Winger, Quinton A., advisor; Bailey, Susan M., committee member; Duval, Dawn L., committee member (Colorado State University. Libraries, 2014)
Ovarian cancer is the fifth most deadly cancer among women in the United States and the most lethal gynecological malignancy in the world. Recent studies reveal that human tumor cells release cell-secreted vesicles called exosomes. Exosomes are endosome-derived vesicles containing bioactive materials, including RNAs and miRNAs that can be detected in body fluids. Importantly, pluripotency factor LIN28, a regulator of let-7 miRNAs, is present in ovarian cancer cells. High LIN28A and low let-7 miRNA levels are associated with aggressive IGROV1 human ovarian cancer cells (Piskounova et al., 2011) so we compared this to low LIN28A and high let-7 miRNA levels in less aggressive OV420 human ovarian cancer cells. Moreover, let-7b, let-7c, let-7g, and let-7i miRNA signatures were also present in their secreted exosomes. We hypothesized that ovarian cancer cell-secreted exosomes are taken up by target cells and induce changes in gene expression and cell behavior. Our data revealed that IGROV1 secreted exosomes taken up by HEK293 cells lead to significantly higher LIN28A mRNA levels, but not LIN28A protein levels and did not significantly change LIN28B mRNA or protein levels. However, IGROV1 exosome exposure to HEK293 cells did significantly increase invasion and migration. In addition, various genes involved in epithelial-mesenchymal transition, including TIMP1 (25-fold higher), NOTCH1 (11-fold-higher), SNAI1 (SNAIL) (7-fold higher), CDH1 (6-fold higher), (MMP9 (4-fold higher), and ZEB1 (3-fold higher), were significantly higher in HEK293 cells following uptake of IGROV1 secreted exosomes. We also postulated that ovarian cancer cell-secreted exosomes contain a distinct RNA signature capable of inducing phenotypic changes in target cells, as well as distinguishing aggressive, advanced ovarian exosomes from less aggressive ovarian exosomes. Since IGROV1 cells are a more aggressive epithelial ovarian cancer cell line, while OV420 cells are a less aggressive cell line, we performed RNAseq transcriptome analysis on exosomes from IGROV1 cells and exosomes from OV420 cells. The results yielded 312 differentially expressed RNAs. Future studies will allow us to detect the RNAs present in exosomes from urine in individuals with early stage versus late stage ovarian cancer. This may enable investigators to distinguish a poor prognosis group from a good prognosis group leading to a potential biomarker for ovarian cancer detection. Data from this study is important for elucidating the role ovarian cancer cell-secreted exosomes have on early metastasis and tumor progression, an area in ovarian cancer biology in critical need of advancement.
Keywords: miRNAs; exosomes; LIN28; let-7